'Armament in depth' or 'armament in breadth'? German investment pattern and rearmament during the Nazi period1. (10th July 2012) - SCHERNER, JONAS
<x xml:space="preserve">Abstract</x> Today, most scholars agree that Nazi Germany did not follow a premeditated Blitzkrieg strategy in the late 1930s and at the beginning of the Second World War. However, the question of the extent to which Germany's economy had been prepared for a longer war is still debated because statistical information on Germany's investment pattern is fragmentary and data on the structure of prewar German military expenditure are not available. Relying on newly discovered sources, this article closes these gaps. The Nazi regime clearly shifted its investment towards preparation for war from the mid‐1930s on, and though armaments purchases stagnated during the period from 1937 to 1939, investment in munitions industries grew considerably. Consequently, during the late 1930s the Nazis pursued a 'sustainable' rearmament strategy necessary for fighting a longer war. Yet, despite massive capacity enlargements in the munitions industries, total German investment was not unusually high by today's definition because contemporary figures included a significant amount of armaments purchases.